Protective efficacy of a live attenuated vaccine against Argentine hemorrhagic fever. AHF Study Group - Maiztegui, Julio I. (1998)
Fil: Maiztegui, Julio I. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Virales Humanas; Argentina.